IMPACTS OF TOURISM DEVELOPMENT IN MALINDI: AN ANALYSIS OF GENDER DIFFERENCES IN PERCEPTION - WANJOHI KIBICHO (Centre For Tourism Planning and Development, 2005)
Tourism is the largest component ofMalindi's local economy. The growth ofthe industry is not without some socio-cultural impacts in the coast region, thus calling for a critical examination of tourism development and the hosts' socio-cultural dynamics. This paper investigates the Malindi residents' perceptions ofthe socio-cultural implications resulting from tourism. Two months of interviews revealed that the Malindi residents fully supported the present levels of tourism development and would like the industry to expand. However, they identified several impacts, both positive and negative, that tourism had on the destination. The study findingsconfirmed that those respondents who economically relied on tourism had more positive attitudes than those who did not depend on it.